Chemical Castration in Perpetrators of Sexual Violence - Hudi Winarso; Abraham Arwinta Sakti; Irene Oktadiana Setijo (Jurnal Indonesia Sosial Teknologi, 2024)
Regulations on chemical castration for perpetrators of sexual violence have been stipulated in the legislation in Indonesia, Law 17 of 2016. Then followed up with Government Regulation (PP) NO 70 OF 2020 which regulates in more detail the chemical castration procedure. However, at the level of implementation, medical and bioethical perspectives, there are still pros and cons. The paradigm of the group that agrees to perform chemical castration on perpetrators, the act of chemical castration causes a decrease in sex hormone (testosterone) levels, thus helping perpetrators manage sex drive more controllable. The paradigm of the group that does not agree on the act of chemical castration, from the aspect of low levels of sex hormones, will cause discomfort or health problems in the perpetrator. On the other hand, the performing physician believes that the doctor's job is to help, not cause discomfort. Medical studies and bioethical studies of chemical castration in perpetrators of sexual violence can improve the understanding of holistic management